Shock Enhanced [C ii] Emission from the Infalling Galaxy Arp 25 - Dario Fadda; Jessica S. Sutter; Robert Minchin; Fiorella Polles (The Astrophysical Journal, 2023)
We present SOFIA observations with HAWC+ and FIFI-LS of the peculiar galaxy Arp 25, also known as NGC 2276 or UGC 3740, whose morphology is deformed by its impact with the intragroup medium of the NGC 2300 galaxy group. These observations show the first direct proof of the enhancement of [C ii ] emission due to shocks caused by ram pressure in a group of galaxies. By comparing the [C ii ] emission to UV attenuation, dust emission, PAH, and CO emission in different regions of the galaxy, we find a clear excess of [C ii ] emission along the impact front with the intragroup medium. We estimate that the shock due to the impact with the intragroup medium increases the [C ii ] emission along the shock front by 60% and the global [C ii ] emission by approximately 25% with respect to the predicted [C ii ] emission assuming only excitation caused by stellar radiation. This result shows the danger of interpreting [C ii ] emission as directly related to star formation since shocks and other mechanisms can significantly contribute to the total [C ii ] emission from galaxies in groups and clusters.